Improving Efficiency of Disinfection of Water for Non-contact UV System - AR Mesdaghinia; F Vaezi; AH Mahvi; K Naddafi; M Alimohammadi (Iranian Journal of Public Health, 2009)
Background: The goal was to upgrade and/or uprate the traditional non-contact array by producing few modifications in the configuration of this model in order to maximize light receiving of water from the UV lamp and a better disinfection. Methods: An innovative non-contact model was made with a design based on irradiation of water, which was flowing as two thin waterfalls around a UV lamp in order to have direct germicidal rays from all positions of the lamp. By this water circulating and traditional water flow in an ordinary canal below the lamp, UV light would reach every drop of water effectively. Another model which had been studied was a simple stair type design in which a bare lamp was fixed over the shiny steel steps. Results of water disinfection in two flow rates of 12 and 24 L/min were compared with traditional design at exactly similar conditions. Results: Disinfection in this new model produced more reduction in fecal coliforms concentration than the traditional array and the inactivation efficiency was specified to be 3.65 log reduction compared to 2.93 log, in the turbidity of 0.5 NTU. Besides, this new model was quite capable in disinfection of water with high turbidities up to 20 NTU. Conclusion: The reduction in disinfection efficiency at higher flow rates for new model was much less than traditional array. Results of water disinfection in the simple stair type were not wonderful and even it was less satisfactory compared to traditional model. The reason is that the flow of water was not set parallel to the length of the lamp.